DEVELOPING KAMISHIBAI MEDIA FOR WRITING NARRATIVE TEXT AT JUNIOR HIGH SCHOOL - Fitri Anisah Sitorus and Rafika Dewi Nasution (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2018)
The objective of this study was to develop Kamishibai media based on students’ needs. Research and Development was used as the research method. Research procedure was modified into four steps: Evaluation and Need Analysis, Media Design, Validation and Revision, and Final Production. The subject of this study was class VIII students of Mts. Muallimin Univa Medan, consisting of 44 students. The data were collected by giving Questionnaire to the students’ and interviewing to the teacher. The products had validated by experts validation (Material and Media). The average scores is 81 % from English Lecture and 84 % from English Teacher and the total average scores is 83 %. It means that developing Kamishibai media categories is relevant or appropriate for VIII Grade student of Mts. Muallimin Univa Medan.